PREPARATION OF FUTURE TEACHERS OF MUSICAL ART TO ARTISTIC AND AESTHETIC EDUCATION OF ADOLESCENTS - Natalііa Tararak (Vasyl Stefanyk Precarpathian National University, 2018)
The article reveals the peculiarities of the artistic and aesthetic education of adolescents, clarifies the essence of the training of future musical art teachers, defines the content of the structural components of readiness for such activity as a result of professional training. The system of training of future musical art teachers for artistic and aesthetic education of adolescents in the educational process is substantiated. The criteria and indicators of readiness levels of future musical art teachers for artistic and aesthetic education of adolescents are clarified.Artistic and aesthetic education is considered as a process of purposeful forming of aesthetic consciousness and aesthetic attitude of the individual to the world around and art through its attachment to the values of artistic culture, forming the ability to allocate an aesthetic component in the content of works of art and give them an assessment of the position of their own aesthetic experience accumulated as a result of artistic and creative activity. It is proved that the definition of the peculiarities of the artistic and aesthetic education of adolescents is conditioned not only by the specifics of this process, but also by the age-old peculiarities, the leading activity, the main tumors. In determining this, there are such spheres as personal, social and cognitive. The process of perception of works of art should be carried out in stages, namely: emotional setting, perception and analysis of interpretation. In this way, the teenager's development will be provided with the above-mentioned spheres.The pedagogical conditions of successful training of future teachers of musical art for the artistic and aesthetic education of adolescents are singled out, namely: 1) the creation of an artistic and aesthetic educational environment in the educational institution; 2) deepening the content of all sections of the professional training of future teachers with issues, measures of artistic and aesthetic orientation; 3) involvement of students in various types of activities (executive, educational, extracurricular educational, practical (pedagogical practice). Key words: teenager, future teacher of musical art, preparation, readiness for artistic and aesthetic education of a teenager.